An account on teaching an english content course in finances Enseñanza del inglés basada en contenidos: experiencia de un curso de finanzas - Jorge Restrepo G (Universidad de La Sabana, 2007)
This paper presents a brief description of English Content Based Instruction (CBI) as a process in which the student gains mastery of the language (procedural knowledge) and mastery of the subject learned (declarative knowledge) along with the characteristics of the integration of the teaching process. Also, the author describes his experiences in planning and teaching a course in Financial Analysis using the techniques of CBI and student-centered learning in addition to the tools and procedures used in performing this task. Furthermore the experiences of other universities in giving CBI courses are analyzed in the light of this experience. The result of a survey about the perception of the course among a representative sample of the students is presented and discussed. Finally the paper presents an analysis of a survey which suggests the importance of the CBI approach in teaching finance in English En este artículo se presenta una breve descripción de la Enseñanza de Inglés Basada en Contenidos (CBI), como un proceso en el cual el alumno adquiere dominio de la lengua (conocimiento procedimental), así como dominio de la asignatura estudiada (conocimiento declarativo), mediante un proceso de enseñanza que integra lengua y contenido. El autor describe sus experiencias en la planeación y enseñanza de un curso de análisis financiero utilizando las técnicas de CBI y de aprendizaje centrado en el estudiante, además de las herramientas y procedimientos más tradi cionales. También se analizan las experiencias de otras universidades que imparten CBI, a la luz de nuestra propia experiencia. Se presenta y discute el resultado de una encuesta sobre la percepción del curso por parte de una mues tra representativa de estudiantes. Finalmente, se presenta el análisis de una encuesta, que sugiere la importancia del enfoque CBI en la enseñanza de finanzas en inglés